Development and Evaluation of Novel Electronic Medical Record Tools For Avoiding Bleeding After Percutaneous Coronary Intervention. Issue 22 (19th November 2019) - Ebinger, Joseph; Henry, Timothy; Kim, Sungjin; Inkelas, Moira; Cheng, Susan; Nuckols, Teryl
Abstract : Background: Bleeding remains the most common complication of percutaneous coronary intervention. Guidelines recommend assessing bleeding risk before percutaneous coronary intervention to target use of bleeding avoidance strategies and mitigate bleeding events. Cedars‐Sinai Medical Center undertook an initiative to integrate these recommendations into the electronic medical record. Methods and Results: The intervention included a voluntary clinical decision alert to assess bleeding risk before percutaneous coronary intervention, a bleeding risk calculator tool based on the NCDR (National Cardiovascular Data Registry) risk prediction model and, when indicated, a second alert to consider 4 bleeding avoidance strategies. We tested for changes in the use of bleeding avoidance strategies and bleeding event rates by comparing procedures performed before versus after implementation of the electronic medical record–based intervention and with versus without use of the bleeding risk calculator tool. Use of radial access increased (47.6% versus 64.8%; P <0.001) and glycoprotein IIb/IIIa inhibitors decreased (12.8% versus 3.17%; P <0.001) from before to after implementation, though risk‐adjusted bleeding event rates were stable (odds ratio, 0.82; P =0.164), even for high‐risk procedures. Use versus nonuse of the bleeding risk calculator tool was associated with increased radial access and reductions in glycoprotein IIb/IIIa inhibitors, but no change in bleeding events. Conclusions: Integrating guideline recommendations into the electronic medical record to promote assessments of bleeding risk and use of bleeding avoidance strategies was feasible and associated with changes in clinical practice. Future work is needed to ensure that bleeding avoidance strategies are not overused among lower‐risk patients, and that, for high‐risk patients, the potential benefits of elective percutaneous coronary intervention are carefully weighed against the risk of bleeding.